Cytotoxicity Effectiveness of Biosynthesized Silver Nanoparticles on Breast Cancer T47D Cell Line, Using Macro Algae Laurencia caspica Extract - Ali Salehzadeh (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām, 2018)
Introduction: Over the past years, silver nanoparticles (AgNPs) due to their anti-angiogenesis, anti-bacterial, and anti-cancer activity have attracted researchers’ interests. The aim of this study was to evaluate the cytotoxicity effects of biosynthesized AgNP using red macroalgae Laurencia caspica on human breast cancer (T47D) cells.   Materials & Methods: In this experimental study, the biosynthesis of AgNPs was evaluated, using Laurencia caspica.The characterization of developed AgNPs was performed through ultraviolet-visible (UV-vis) spectroscopy, scanning electron microscopy (SEM), and transmission electron microscopy (TEM). The T47D and MRC-5 cell lines were treated with various concentrations of fabricated AgNPs for 24 and 48 hours, rspectively. The viability effects of cells and half maximal inhibitory concentration) IC50 (were evaluated by MTT assay.   Findings: The fabricated AgNPs were monitoring characteristic surface Plasmon resonance peak at around 420nm. The SEM and TEM results for size and morphological studies of AgNPs showed that nanoparticles were of spherical shape ranging from 10 to 50 mm. The MTT results demonstrated that AgNPs significantly decreased the viability of cells in dose-and time-dependent manners. The IC50 value of nanoparticles for T47D and MRC-5 cell lines were calculated as 29.37 mg/mL and 42.13 mg/mL 48 hours following treatment with nanoparticles, respectively.   Discussion & Conclusions: Based on the current study, the biosynthesized AgNPs can cause more cytotoxic effects on breast cancer cells compared to the normal cells. Thus, they can be considered a promising procedure for the treatment of breast cancer.